Geopoba as a soil stabilization material - Mukri, Mazidah; Zainuddin, Atiqah Najwa; Che Lat, Diana (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This research-enhanced soil liners are used in modern landfills to contain waste and the study explores the use of green technology geopolymers as an additive. Geopolymer was used in this research in considering the main material that could enhance laterite's properties in the performance of hydraulic conductivity in soil liner application. This study uses palm oil boiler ash mixed with sodium hydroxide and sodium silicate to make geopolymer paste. Boiler ash is another industrial waste product from the combustion of coal. A boiler ash-based geopolymer was mixed with laterite mixed with different percentages (5,10,15, and 20%) to improve soil liner application properties. The objective of this research is to determine the optimum percentage of geopolymer mixed with laterite as an additive for reducing hydraulic conductivity. An empirical model has been developed based on the results of this study, showing that increases in geopolymer content result in a decrease in hydraulic conductivity. As an alternative to lengthy laboratory tests that take a long time, the empirical model is designed to predict hydraulic conductivity, k, for landfill soil liners without requiring long-term laboratory testing.